CRYPTO WARS the fight for privacy in the digital age. - Jarvis, Craig ([S.l.] : CRC PRESS, 2020)
The crypto wars have raged for half a century. In the 1970s, digital privacy activists prophesied the emergence of an Orwellian State, made possible by computer-mediated mass surveillance. The antidote: digital encryption. The U.S. government warned encryption would not only prevent surveillance of law-abiding citizens, but of criminals, terrorists, and foreign spies, ushering in a rival dystopian future. Both parties fought to defend the citizenry from what they believed the most perilous threats. The government tried to control encryption to preserve its surveillance capabilities; privacy activists armed citizens with cryptographic tools and challenged encryption regulations in the courts. No clear victor has emerged from the crypto wars. Governments have failed to forge a framework to govern the, at times conflicting, civil liberties of privacy and security in the digital age--an age when such liberties have an outsized influence on the citizen-State power balance. Solving this problem is more urgent than ever. Digital privacy will be one of the most important factors in how we architect twenty-first century societies--its management is paramount to our stewardship of democracy for future generations. We must elevate the quality of debate on cryptography, on how we govern security and privacy in our technology-infused world. Failure to end the crypto wars will result in societies sleepwalking into a future where the citizen-State power balance is determined by a twentieth-century status quo unfit for this century, endangering both our privacy and security. This book provides a history of the crypto wars, with the hope its chronicling sets a foundation for peace.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Cryptography; POLITICAL SCIENCE / Political Freedom & Security / Intelligence; COMPUTERS / History; Privacy, Right of; Data encryption (Computer science) -- Political aspects; Data encryption (Computer science) -- Law and legislation